Pyrocarbon Humeral Head in a Shoulder Hemiarthroplasty: Preliminary Results at 3 Years Follow-Up and Review of the Current Literature - Eva Campos-Pereira; Luís Henrique-Barros; Rui Claro (Case Reports in Orthopedics)
Shoulder hemiarthroplasty is a viable option in young patients with an intact rotator cuff in order to preserve the native glenoid. To avoid the dreaded and expected wear of the glenoid in very active shoulders, implants with humeral head coated with a high resistant and elastic material—pyrolytic carbon—are now an option. The authors present the first pyrocarbon coated hemishoulder arthroplasty performed at our Orthopedic Department in a patient with osteonecrosis of the humeral head. At three years of follow-up, the patient is pain free and without limitations in his daily work. The Constant score was applied pre- and postoperatively, and an improvement of 32 points was reported. Larger cohorts with long-term follow-up are required to confirm our promising results.